Endoscopic ultrasonography‐guided cholecystogastrostomy using a lumen‐apposing metal stent as an alternative to extrahepatic bile duct drainage in pancreatic cancer with duodenal invasion. (25th April 2013) - Itoi, Takao; Binmoeller, Kenneth; Itokawa, Fumihide; Umeda, Junko; Tanaka, Reina
Abstract : Various approaches to biliary drainage, especially endoscopic ultrasonography (EUS)‐guided drainage, have become commonly used as an alternative method for biliary decompression for malignant biliary obstruction. Occasionally, however, duodenal obstruction and non‐dilated intrahepatic bile duct impede conventional EUS‐guided biliary drainage. Herein, we describe a case of cholecystogastrostomy successfully carried out using a newly developed fully covered lumen‐apposing self‐expandable metallic stent (SEMS). EUS‐guided cholecystogastrostomy should be considered an option for biliary decompression. This is aparticularly ideal alternative if the patient has duodenal strictures with or without a duodenal metal stent and a non‐dilated intrahepatic bile duct, which suggests the impossibility of choledochoduodenostomy and hepaticogastrostomy. Furthermore, the newly developed fully covered lumen‐apposing SEMS seems ideal for EUS‐guided cholecystoenterostomy.